Lincoln's sense of humor - Carwardine, Richard (Concise Lincoln library., 2017)
"Abraham Lincoln was the first president consistently to make storytelling and laughter tools of office. This book shows how his uses of humor evolved to fit changing personal circumstances, and explores its versatility, range of expressions, and multiple sources"--